Theory of mind and metacognition in migraine patients (Annals of Medical Research, 2024)
Aim: Theory of Mind (ToM) and metacognition are distinct psychological constructs, involving the understanding of emotions and mental states in oneself and others. Despite their relevance, these concepts have been poorly investigated in adult migraine patients and the findings in the existing literature are inconsistent. Our objective was to assess whether the theory of mind skills and metacognitive abilities were impaired in individuals with migraine.Materials and Methods: We included 23 individuals with Episodic Migraine (EM), 19 with Chronic Migraine (CM), and 30 Healthy Controls (HCs). To assess Theory of Mind (ToM) skills and metacognitive abilities, participants, including both EM and CM patients and HCs, completed the Beck Depression Inventory (BDI), Reading Mind in the Eyes test (RMET), and Metacognition Scale (MCQ). EM patients were evaluated interictally (the 72-hour headache-free period before and after the evaluation) and CM patients during the headache-free period.Results: Patients with CM exhibited higher BDI scores compared to both EM patients and HCs (p=0.018, p=0.032, respectively). Furthermore, the RMET scores of CM patients were significantly lower than those of the HCs (p=0.011). MCQ scores did not show significant differences between the groups (p=0.288). Notably, MCQ scores were positively correlated with BDI scores (r=0.42, p
Keywords: Migraine; Theory of mind; Metacognition; Social cognition